Most wanted [compact disc] - Duff, Hilary, 1987- (Hollywood Records, 2005)
Singer/actress Hilary Duff has put together a collection of her greatest hits, remixes, and new songs. Most Wanted features the hits Come Clean and So Yesterday along with the new singles Wake Up and Beat Of My Heart.